Personal constructs of patients with eating disorders - Pačešiūnaitė, A.; Čekuolienė, D. (Psichologija, 2010)
Objective. To examine the personal constructs system in female patients with eating disorders. Method. All subjects were invited to take part in a semi-structured interview which included completion of a type of repertory grid known as SELF-GRID. The SELF-GRID was chosen as specifically suited to this study having been devised by E. Button (1993) with the aim of exploring personal constructs of patients with eating disorders. In this study, a repertory grid of 11 elements (five versions of oneself and six elements of other people) was presented to 20 female subjects suffering from anorexia nervosa and bulimia nervosa, and 20 matched control subjects. Results. The main difference between the two groups was found to be the greater tendency of patients with eating disorders to construe in a narrow “tight construing” manner utilising less multidimensional personal constructs than the control group. This means that these patients with eating disorders were less cognitively complex than the control subjects. On the total percentage of variance contributed by the first three principal components, there was a significant difference (eating disorder group 83.12 %; control group 78.24 %; t = 2.465; p < 0. 05). The use of narrower systems of personal constructs provides fewer alternatives for construing oneself and other people. Such a constriction of alternatives might arise from a desire for greater predictability and control. In this situation, people with more multidimensional constructs can be a source of danger to the narrower system of personal constructs, as they might challenge and invalidate these constructs. This may explain why patients with eating disorders can gradually withdraw from socialising. The content of constructs was also analysed. Surprisingly, no central constructs related to weight, eating or appearance were found. The further detailed work is needed to understand this finding, as this might reflect the denial of the problem or, on the contrary, indicate that disturbed eating is just a manifestation of other underlying problems such as restricted negative emotionality, perfectionism, and high levels of achievement. Results of this study provide some evidence of a shared underlying problem, “goal orientation” being the consistent strong main theme of the personal constructs of patients with eating disorders. Patients with eating disorders usually focus narrowly on getting thinner, perhaps in the naïve hope that this will solve their underlying problems. The number of constructs elicited by the SELF-GRID was compared between the groups, and there was no significant difference. Neither was there a significant difference between eating disorder and control groups in the measures of positivity / negativity of construing. Conclusions. The personal construct systems of patients with eating disorders were less cognitively complex as compared with control subjects, although there was no difference in the number of elicited constructs. The main topic of the personal constructs of patients with eating disorders was “goal orientation”.